Pemberdayaan Masyarakat Melaui Pembuatan Puding Sedot Susu Sapi untuk Peningkatan Pendapatan Peternak di Dusun Sereng, Desa Kemiri, Kecamatan Puspo, Kabupaten Pasuruan - Mirza Andrian Syah; Andru Armana; Toriq Aulia Rahman (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
This community service program aims to increase the use of abundant milk from dairy cows in Sereng Hamlet, Kemiri Village, Puspo District, Pasuruan Regency, through training in making sucked pudding or pudot. The local community, which previously only sold raw milk to collectors with low economic value, is trained to process milk into value-added products that are more attractive to consumers using direct practical methods to facilitate community understanding and skills at every stage, starting from socialization, training theoretically, hands-on practice, to digital marketing. The results of the activity showed that participants not only mastered the technique of processing pudot with various flavors, but also utilized digital platforms to reach a wider market. Apart from improving technical and economic skills, this program motivates communities to innovate and be independent in managing local products. With ongoing support and evaluation, it is hoped that the people of Sereng Hamlet can create new, sustainable business opportunities and strengthen the village economy through diversifying dairy products. This program is expected to become a model for rural economic development that can significantly improve the quality of life of local communities